Standarisasi dan Profesionalisas Implementasi Kurikulum 2013 Revisi Dalam Era Industri 4.0 - Chira Saidah Yusrie; Ernawati Ernawati; Ahmad Mudrikah; Ujang Cepi Barlian; Arman Paramansyah (Jurnal Dirosah Islamiyah, 2022)
The revised 2013 curriculum is one of the government's programs to achieve the educational goals of the Indonesian people who are highly insightful, mastering science and technology. Thus, the revised 2013 curriculum is expected to be able to solve various problems that are being faced in the world of education. The implementation of the revised 2013 curriculum is expected to produce people who are productive, creative, innovative and can always protect and care for nature in Indonesia. This is possible, because this curriculum is based on character and competence, which conceptually has several advantages, one of which is natural (contextual), because it departs, focuses and leads to the nature of students to develop various competencies according to their respective competencies. Implementation of the 2013 Curriculum during the pandemic era 4.0 is still lacking. Teachers must provide the best facilities for students regarding the delivery of material, content and foster a passion for learning so that their skills are honed. So they can improve learning outcomes. For madrasas, the implementation of the revised 2013 curriculum during the 4.0 pandemic era was extremely difficult because of the character of the students, the potential of madrasa students was very difficult to know when implementing the 2013 curriculum. 4.0 which is a very difficult challenge, even though socialization and teacher training have been carried out, but not all teachers understand it well. In the implementation of the revised 2013 curriculum, there are many obstacles faced by subject teachers in improving student learning outcomes. Some of these obstacles are: facilities and infrastructure, rating, learning resources, students tend to be passive. Keywords : 2013 curriculum revision, Covid-19 pandemic, Curriculum Implementation